Modelagem para mensuração da competitividade na geração de energia fotovoltaica - Rosa, Carmen Brum (2016)
The photovoltaics is seen internationally regarded as a very promising technology. It is estimated that Brazil currently has a high capacity for solar power generation. Furthermore, from a strategic point of view, Brazil has a number of favorable natural features, such as high levels of insolation and great quality quartz reserves that can generate important competitive advantage for the production of silicon with high purity, photovoltaic cells and modules of high added value. In order to make the generation of Brazilian photovoltaics globally competitive, some government incentives are providing the growth, expansion and modernization of this technology. Despite the favorable environment in which it is the generation of electricity from renewable sources there are still gaps that undermine the competitiveness of plants that generate energy from photovoltaic source, such as the qualifications of labor available, the adequacy of suppliers to their demands and the great need for investment in technology. In this sense, this master thesis aimed to propose a modeling able to measure the level of competitiveness in the generation of photovoltaic energy, based on a bibliographical and documentary research on industry characteristics were raised 41 performance indicators, using for both assumptions regarding the Key Performance Indicators (KPIs) and elements of the multi-criteria approach to decision support. The proposed survey instrument was applied in two Brazilian solar plants, a research center on renewable energy the European Union and the metal-mechanic sector industry that has a solar system in operation. The test evaluation phase generated an index that represents the competitive performance of each of the participating research companies, Usina Eletrosul had a competitive percentage of 46.80%, the company Tramontina Eletrik 58%, Usina Tauá 74.75 % and 76.64% Cener, allowing a comparative discussion of the results. Later, they were recommendations proposed able to leverage the competitiveness of Usina Eletrosul, involving the simulation of indicators that showed unsatisfactory levels, demonstrating the relevance of modeling to increase the competitiveness of companies generating photovoltaic front power to the scenario at hand.